VD_FINDINFO Jug / 2024 / 514 vom 17. Dezember 2024 - VD Tribunal cantonal (2024)
CLAH 80, ENLÈVEMENT D'ENFANTASPECTS CIVILS, GUINÉE, RETRAITVOIE DE DROIT | 14 LF-EEA, 241 al. 3 CPC (CH), 241 CPC (CH), 26 al. 2 LCaH 80